Associations between chronotype, social jetlag, and weekday sleep in women with irritable bowel syndrome. (4th May 2021) - Yang, Pei-Lin; Burr, Robert L.; de la Iglesia, Horacio O.; Buchanan, Diana T.; Ward, Teresa M.; Landis, Carol A.; Heitkemper, Margaret M.
ABSTRACT: Sleep deficiency is well-documented in individuals with irritable bowel syndrome (IBS). Sleep deficiency includes poor sleep quality and an inadequate amount of sleep, and is a modifiable risk factor for IBS symptom exacerbations. Prior studies in other populations have identified chronotype and social jetlag (SJL) as important determinants of sleep outcomes. However, chronotype and SJL have not been examined in women with IBS. We used multiple linear regression analyses to determine whether chronotype and SJL are associated with sleep outcomes during weekdays among women with IBS predominant constipation (IBS-C), IBS with predominant diarrhea (IBS-D), and healthy control (HC) women. This sample included 62 women with IBS (IBS-C = 29, IBS-D = 33) and 58 HC women who completed a 28-day daily diary from two study cohorts. The average age of the participants was 30.1 (SD 7.2) years. Chronotype was estimated from daily diary data with the average mid-sleep time on weekends (MSW we ). SJL was calculated by subtracting the average mid-sleep time on weekdays from MSW we . Sleep outcomes included diary assessments of sleep quality, sleep need met, and restorative sleep during weekdays. In HCs, later chronotype was predictive of lower sleep quality (β = −0.19, p < .01), a perception of sleep need not met (β = −0.17, p < .001), and a less restorative sleep during weekdays (β = −0.15, p = .073), whereas SJL was not associated with sleep outcomes. Similar to HCs, earlier chronotypes in women with IBS-C reported better sleep quality and more sufficient sleep need met and restorative sleep during weekdays than later chronotypes (all p > .05). Compared to HCs, the relationships of chronotype with weekday sleep outcomes in the women with IBS-D were in the opposite directions (all p < .05). This exploratory study suggests that chronotype expression may reflect the temporal associations of sleep outcomes within IBS bowel pattern predominance subgroups, particularly sleep quality and sleep need met. Additional investigations are warranted to examine whether specific temporal attributes of symptoms and/or symptom severity associated with IBS subgroups contribute to chronotype expression.